AB1046 Can MRI of the Metatarsophalangeal Joints Differentiate Mechanical from Early Inflammatory Metatarsal Pain?. (9th June 2015) - Cosso, C.; Pastorino, M.; Barbieri, F.; Aleo, E.; Migone, S.; Prono, V.; Cutolo, M.; Cimmino, M.A.
Abstract : Background: Metatarsal pain is a frequent complaint in the general population. It is usually mechanical and associated with a variety of risk factors, including female sex, anatomical changes of the forefoot, joint laxity, overweight, and high-heeled shoes. In a minority of patients, metatarsal pain can be a symptom heralding an early arthritis, a condition sharing some of the previously mentioned risk factors. In this setting, where laboratory examinations and conventional radiography are often silent, MRI could be theoretically of help in the differential diagnosis by investigating synovitis, bone marrow oedema (BME), and erosions. BME, however, may be present also in traumatic, degenerative, and overload-associated conditions, such as osteoarthritis. To our knowledge, data regarding the MRI comparison between degenerative and inflammatory metatarsal pain are scanty. Objectives: To investigate if MRI of the metatarsophalangeal (MTP) joints could be useful in the differential diagnosis of mechanical MTP pain as compared to early arthritis. Methods: 10 patients with mechanical MTP pain (9 women, mean age 51.1±12.5 years, disease duration 14.1±12.2 months), without a history or clinical findings suggestive of arthritis or psoriasis were studied. They were compared to 13 patients with early (<6 months) rheumatoid arthritis (RA) (11 women, mean age 47.5±17.1 years, disease duration 3.3±2 months), 8 patients with long-standing RA (7 women, mean age 57.5±11.7 years, disease duration 40.1±27 months), and 8 patients with seronegative spondyloarthritides (SeS, 6 psoriatic arthritis and 2 reactive arthritis, 5 women, mean age 50.7±9.2, median disease duration 24 months, range 1-216 months). The diagnosis of arthritis was based on the relevant criteria. MRI was performed with a 0.2T extremity dedicated machine (Artoscan C, Esaote, Genova, Italy) using Turbo 3D (erosions) and STIR (synovitis and BME) sequences: Turbo 3D T1-weighted sequences (TR/TE=35/16 ms; matrix=192x160; FOV=140x140; slice thickness 0.8 mm; interslice gap 0 mm) in the coronal plane with subsequent reconstruction of the remaining planes; coronal and axial STIR sequences (TR/TE=1500/24 ms [coronal] and 2400/24 [axial]; matrix=192x160 [coronal] and 192x144 [axial]; FOV=160x160; slice thickness 3 mm [coronal] and 4 mm [axial]; interslice gap 0.3 mm [coronal] and 0.4 mm [axial]). All lesions were scored as present or absent. Results: Table 1 reports the results of the study. Conclusions: The only MRI feature differentiating mechanical MTP pain from arthritis was synovitis. BME was significantly more frequent only in established RA. MRI can help in the differential diagnosis between degenerative metatarsal pain and early arthritis because of the increased frequency of synovitis in the latter. Disclosure of Interest: None declared